Determination of the ion collection efficiency of the Razor Nano Chamber for ultra‐high dose‐rate electron beams. Issue 7 (20th May 2022) - Cavallone, Marco; Gonçalves Jorge, Patrik; Moeckli, Raphaël; Bailat, Claude; Flacco, Alessandro; Prezado, Yolanda; Delorme, Rachel
Abstract: Background: Ultra‐high dose‐rate (UHDR) irradiations (>40 Gy/s) have recently garnered interest in radiotherapy (RT) as they can trigger the so‐called "FLASH" effect, namely a higher tolerance of normal tissues in comparison with conventional dose rates when a sufficiently high dose is delivered to the tissue. To transfer this to clinical RT treatments, adapted methods and practical tools for online dosimetry need to be developed. Ionization chambers remain the gold standards in RT but the charge recombination effects may be very significant at such high dose rates, limiting the use of some of these dosimeters. The reduction of the sensitive volume size can be an interesting characteristic to reduce such effects. Purpose: In that context, we have investigated the charge collection behavior of the recent IBA Razor™ Nano Chamber (RNC) in UHDR pulses to evaluate its potential interest for FLASH RT. Methods: In order to quantify the RNC ion collection efficiency (ICE), simultaneous dose measurements were performed under UHDR electron beams with dose‐rate‐independent Gafchromic™ EBT3 films that were used as the dose reference. A dose‐per‐pulse range from 0.01 to 30 Gy was investigated, varying the source‐to‐surface distance, the pulse duration (1 and 3 μs investigated) and the LINAC gun grid tension as irradiation parameters. In addition, the RNC measurements were corrected from the inherent beam shot‐to‐shot variations using an independent current transformer. An empirical logistic model was used to fit the RNC collection efficiency measurements and the results were compared with the Advanced Markus plane parallel ion chamber. Results: The RNC ICE was found to decrease as the dose‐per‐pulse increases, starting from doses above 0.2 Gy/pulse and down to 40% of efficiency at 30 Gy/pulse. The RNC resulted in a higher ICE for a given dose‐per‐pulse in comparison with the Markus chamber, with a measured efficiency found higher than 85 and 55% for 1 and 10 Gy/pulse, respectively, whereas the Markus ICE was of 60 and 25% for the same doses. However, the RNC shows a higher sensitivity to the pulse duration than the Advanced Markus chamber, with a lower efficiency found at 1 μs than at 3 μs, suggesting that this chamber could be more sensitive to the dose rate within the pulse. Conclusions: The results confirmed that the small sensitive volume of the RNC ensures higher ICE compared with larger chambers. The RNC was thus found to be a promising online dosimetry tool for FLASH RT and we proposed an ion recombination model to correct its response up to extreme dose‐per‐pulses of 30 Gy.